1 - Cultivating Conflict: Agricultural ’Betterment’, the Native Land Husbandry Act (NLHA) and Ungovernability in Colonial Zimbabwe, 1951-196: by Guy Thompson - Guy , Guy (Africa Development, 2004)
in the 1950s, the white minority regime in Zimbabwe launched an ambitious development scheme for peasant agriculture, known as the Native Land Husbandry Act. It was abandoned in 1962 in the face of massive rural opposition. This paper explores the key provisions of this surprising scheme and its origins in the political economy of the colony and the contradictory interests of the settler community. It then looks at why Africans rejected the measure, arguing the NLHA undermined key peasant strategies for production, environmental management, and survival in the colonial order. Peasants initially tried to evade the impositions of the scheme, but then became defiant as the state tried to coerce them to follow the law. Protests spread throughout the country, creating a state of ungovernability that threatened white rule. These developments played a key role in rural mobilisation and the emergence of land-based nationalism in Zimbabwe, factors that continue to shape the political and social landscape today.